The development of adaptation pathways for the long‐term planning of urban drainage systems. (16th April 2019) - Babovic, Filip; Mijic, Ana
Abstract: Cities must adapt their drainage systems to cope with the effects of land use and climate change on growing flood risk. However, the development of robust adaptation strategies remains a challenge due to the deep uncertainty surrounding future conditions. To address this problem, an Adaptation Tipping Points (ATP) approach was utilised to investigate the impacts of future rainfall with respect to increases in both depth and intensity on an urban drainage system. A set of adaptation pathways was generated to assess how the drainage system could be adapted using a range of infrastructure solutions. The most effective combination of adaptations to increase the system's ATP was an increase in system storage followed by green infrastructure solutions to add additional capacity to the system. The methodology enabled no‐regret adaptation by proposing a set of selected interventions that can be incrementally implemented to achieve maximal combined effect. The resulting pathways effectively communicate to decision makers how short‐term solutions allow for long‐term adaptation and sustainable development. The ATP approach proved to be an effective tool for decision‐making that provided a structured approach for the long‐term planning of urban drainage systems.